One plus one is more than two- The making of the population and socio-economic atlas of Nepal - Shrestha, Suresh Man (Journal on Geoinformatics, Nepal, 2005)
Survey Department and Central Bureau of Statistics are two major data producers of HMG Nepal. Survey Department is mainly responsible for producing different types of maps and Central Bureau of Statistics is mainly responsible for conducting censuses. Working together can produce a wide spectrum of products needed for overall national development. This "The population and socio-economic atlas of Nepal" is a good example in this regard. Building a right team exploring and reasons behind the successful production of the atlas. This paper presents some of the major aspectes of the making of "The population and socio-economic atlas of Nepal".